Penggunaan Model Pembelajaran Two Stay Two Stray untuk Meningkatkan Keaktifan Peserta Didik pada Pembelajaran Sejarah di Kelas XII MIPA 1 SMAN 2 Pekanbaru - yanuar alfiqri; Wiwen Indayani (Arden Jaya Publisher, 2022)
This article is a simple scientific work on History learning. This study uses the method of Quantitative Research. Aims to find out the use of the Two Stay Two Stray model to increase the activeness of students in learning history. In learning history, a model is needed to facilitate students' understanding, which so far learning history has mostly used the lecture and memorization method. So we need a new model that will make students better understand the material presented and can apply it in everyday life. This research was conducted at SMA N 2 Pekanbaru with the subjects being class XII students. The results of this study indicate that class XII students are very enthusiastic, active and very communicative in participating in the learning process when using the Two Stay Two Stray learning model when studying, different when only using the lecture method, they tend to be more passive, from here the researcher see that the research carried out can be said to be successful.